PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA BANK GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2009-2012 - Hamidah, Hamidah; Sari, Dian Puspita; Mardiyati, Umi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
The purpose of this study is to know the effect of intellectual capital on financial performance on bank go public listed on the Indonesia Stock Exchange in 2009-2012. The sampel are several bank go public. The research method in this study uses correlation study. The research model in this study employs panel data analysis with random effect approach on model 1a and fixed effect approach on model 1b. The empirical results show that intellectual capital that proxy with Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) have positive significant effect on Earning per Share (EPS) but Structural Capital Value Added (STVA) has negative and no significant effect on Earning per Share (EPS). While, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA) have positive significant effect on Return On Assets (ROA). Keywords: Intellectual Capital, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), Earning per Share (EPS), Return On Assets (ROA)